Analysis of the Value for Money in Measuring the Financial Performance of Pamekasan District Government for Fiscal Year 2017-2021 - Asti Talitha Rahima Widya Paramesti; Armeliza, Diah; Khairunnisa , Hera (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study to determine the financial performance Government of Pamekasan Regency by using the Value for Money concept to measure the level of economical, eficiency and ef ectiveness of the regional finance of the Pamekasan Regency for the 2017- 2021 fisical year. The research used secondary data from the Pamekasan Regency Regional Revenue and Financial Management agency website. This research was conducted by taking data for 5 years. This research is a descriptive study with the object being studied is the data of the Financial Report of Pamekasan Regency Local Government which is the Government’s Regional Revenue and Expenditure Budget Realization Report (RAPBD). The data collection method used is documentation. The data analysis technique used is quantitative descriptive analysis. Based on the results of research on local financial performance Government of Pamekasan regency using the Value for Money concept based on 3 main ratio such as economy, efficiency, effectiveness. The results of the research from an economic level are that in the 2017 to 2021 budget year, the Pamekasan Regency Government succeeded in achieving an economic performance level of between 80.4% and 88% with the "economic" criteria. The average economic level for 5 years is 83.58%, which means it is in the economic category. In terms of efficiency, the research results show that the efficiency level of the Pamekasan Regency Government’s financial performance in 2017-2018 was efficient and in 2019-2021 it was inefficient. The average efficiency level for 5 years is 100.66%, which means it is in the inefficient category. The results of calculating the level of effectiveness of the Pamekasan Regency Government’s financial performance in 2017-2018 were in the "effective" category and in 2019-2021 described "ineffective" in revenue management with an average effectiveness level of 100.7%. Based on the results of these studies, the Value for Money concept is very good to be applied to the Government of Pamekasan Regency because it can comprehensive performance overview.